Mechanical characterization of intralaminar natural fibre-reinforced hybrid composites. (15th October 2019) - Cavalcanti, D.K.K.; Banea, M.D.; Neto, J.S.S.; Lima, R.A.A.; da Silva, L.F.M.; Carbas, R.J.C.
Abstract: The main objective of this work was to investigate the effect of hybridization and the effect of chemical treatments on the mechanical properties of a novel intralaminar natural fibre hybrid composite. Jute, sisal and curauá fibres were selected as natural fibre reinforcements for the epoxy matrix based composites which were produced by hand lay-up technique. The total volumetric fraction used in the fabrication of the hybrid composites was 30% of fibres and 70% of epoxy resin. Tensile, flexural and impact tests were carried out according to ASTM standards to characterize the novel hybrid composites. It was found that the mechanical properties evaluated are significantly improved by addition of the natural fibres to pure jute based composites. The fibre treatments had different effects on the mechanical properties of the hybrid composites. For sisal reinforced hybrid composites, the alkaline treatment had a positive impact on the composite properties (tensile, flexural and impact), while for the jute + curauá hybrid composites the alkali treatment had a negative effect on the tensile and impact properties. The mixed (alkalization + silanization) treatment had a positive effect on the jute + curauá flexural properties, while decreased the flexural properties for the jute + sisal composite. A scanning electron microscopy (SEM) was used to examine the fracture surface of the tested specimens.